Peningkatan Keterampilan Menulis Narasi dengan Model Cooperative Integrated Reading and Composition pada Siswa Kelas IV MI Al-Mukhlisin Kota Jambi - Windha Afriyanti Harahap; Sean Popo Hardi (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
This research was motivated by the low narrative essay writing skills of class IV students at Madrasah Ibtidaiyah Al-Mukhlisin, Jambi City. The aim of this research is to improve the process and skills of writing students' narrative essays using the cooperative integrated reading and composition model in the Madrasah Ibtidaiyah Al-Mukhlisin class in Jambi City. This research is a classroom action research consisting of two cycles. The subjects of this research were students from the Madrasah Ibtidaiyah Al-Mukhlisin class in Jambi City. The research results showed that the average teacher observation score in cycle I was 79 and in cycle II it increased to 89.55 in the "good" category. The results of student observations in cycle I were 73.9 and increased in cycle II to 88.5 in the "good" category. Classical completion of narrative writing skill scores in the pre- cycle obtained an average score of 61.1 in the "Not Good" category. In cycle I, an average score of 79.1 was obtained in the "Pretty Good" category and this increased to 85.7 in the "Good" category in cycle II. It was concluded that the use of the cooperative integrated reading and composition (CIRC) learning model can improve the process and skills of writing narrative essays.